Selected CNS Outcomes Among INSTI Antiretrovirals. (4th October 2017) - Wohl, David; Mills, Anthony; Mera, Robertino; Piontkowsky, David
Abstract: Background: Higher rates of neuropsychiatric events among patients on dolutegravir (DTG) compared with other integrase inhibitors (INSTIs) have been reported from clinic cohorts and one blinded trial. We compared select neurological and psychiatric events in a large sample of patients treated with different INSTIs. Methods: The Quintiles IMS database, which includes pharmacy and medical claims records, was examined for HIV infected patients treated from 2006 to 2016 with DTG (TIVICAY/TRIUMEQ), elvitegravir (EVG, STRIBILD), or raltegravir (RAL, ISENTRESS). The dependent variable outcomes were insomnia/sleep disturbance and depression. A propensity score was created to adjust for variables associated with treatment with a particular INSTI including age, gender, year of initial INSTI exposure, and enrollment time. Multivariate Poisson mixed models were used to generate incidence rate ratios (IRRs). Results: Records for 54, 151 distinct HIV-infected patients treated with DTG, EVG, or RAL were identified. In the multivariate model the rate of insomnia/sleep disturbance events was significantly higher for patients treated with DTG vs. EVG (IRR 1.21 [95% CI 1.09–1.33, P < 0.001]), but was not significantly different when comparing DTG to RAL (IRR 1.04 [95% CI 0.94–1.14, P = 0.459]). Likewise, the rate of incident depression was significantly higher for patients treated with DTG vs. EVG (IRR 1.18 [95% CI 1.09–1.27, P < 0.001], but not when comparing DTG to RAL (IRR 0.93 [95% CI 0.87 – 1.01, P = 0.068]). Conclusion: In this analysis using a large healthcare database, significantly higher adjusted rates of both incident insomnia/sleep disturbances (21% more) and depression (18% more) were found among patients treated with DTG compared with EVG. In contrast, a significant difference in the rates of either outcome was not observed when comparing DTG and RAL. Further studies are warranted to determine the risk of neuropsychiatric events in patients treated with different INSTIs. Disclosures: D. Wohl, Gilead Sciences: Consultant and Investigator, Consulting fee and Research grant; Viiv: Consultant and Investigator, Consulting fee and Research grant; Janssen: Consultant, Consulting fee; Bristol-Myers Squibb: Consultant, Consulting fee; A. Mills, Gilead Sciences: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium; Viiv: Consultant and Investigator, Consulting fee and Research grant; Merck: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium; Janssen: Investigator, Research grant; Bristol-Myers Squibb: Investigator, Research grant; Sangamo Bio Sciences: Investigator, Research grant; R. Mera, Gilead Sciences: Employee and Shareholder, Salary; D. Piontkowsky, Gilead Sciences: Employee and Shareholder, Salary